Future Urban Networks - Griffiths, Jac (AIS - Architecture Image Studies, 2020)
The society of the network is one that is more connected than ever through the ubiquity of cybernetic activity, yet this has been paralleled by fragmentation of space and de-localisation of place. This speculative project explores a re-conception of perceived space in response to contemporary trends in social practice. Contextualised against a backdrop between post-scarcity and singularity, the project encompasses the formation of an urban network fabric that provides a framework for utopian social emergence. An infrastructural armature that produces emergent, machinic artefacts, dispersed along the landscape. The spaces of possibilities developed within this framework, speculate on the merger of virtual and physical space, contending to show a realisation of collective agency within spatial production.